Hospital anxiety and depression - P. Scagliusi; F. Craig; L. Albanese; S. D'Amore; A.R. Carone; M. D'Amore (PAGEPress Publications, 2011)
Objective: The study investigate the presence of depressive disorders in patient who are taken in general hospital, to prevent and reduce the risk of developing a psychological pathology (anxious-depressive symptoms). Methods: We used two tests: 1. General Health Questionnaire (GHQ-12) by Goldberg, a self-report questionnaire, consisting of 12 items, used to estimate the probability of detecting non-psychotic mental disorders and problems in every day's activity. 2. Personal Health Questionnaire (PHQ), a self-report questionnaire, consisting of 10 items. It is a new tool for detecting individuals with ICD-10 depressive disorders, used to estimate the probability to individuate the presence of major depression symptoms, and minor depression symptoms. Tests have been administered to 140 subjects (males' experimental group, 32 subjects; males' control group, 20 subjects; females' experimental group 58 subjects; females' control group, 30 subjects) from eight departments of university hospital, medical faculty, and social services. Results: It can be noted that with GHQ-12, the presence of non-psychotic mental disorders does not come out: just the females' group, experimental and control, shows some problems with insomnia and stress. On the other hand, with PHQ, the presence of no great entity depressive symptoms comes out for all groups. In the experimental groups the quantity of depressive symptoms is greater than in the control groups. Conclusions: We have find the presence of a number of depressive symptoms into a hospitalized population. It is known that detecting such symptoms is important for protection and care of depressive disorders in hospitalized and nonhospitalized populations.